India Traders of the Middle Ages: Documents from the Cairo Geniza. “India Book” by Shelomo Dov Goitein and Mordechai A. Friedman (Leiden: Brill, 2008. 919 pages.) (American Journal of Islam and Society, 2009)
Throughout Antiquity, the Middle Ages, and our current era, the IndianOcean has been the economic backbone of an interconnected global community.This inter-territorial commerce, which feeds a vast network of merchantsfrom the western Mediterranean to the South China Sea, probablyconstitutes the single most important cultural milieu in human history.While many existing studies highlight these networks’ significance andeven a subdiscipline in academia focuses on the “Indian Ocean,” some significantcomponents of the interlinking system are missing. A particularlydifficult problem is the shortage of primary material from the system’s earlierperiods, especially prior to the arrival of the Portuguese and the Dutch.The present volume, which is comprised of annotated and translated lettersof various eleventh- and twelfth-centuryArab Jewish traders who interactedwithin this larger Indian Ocean complex, provides perhaps the most foundationalsource to understand the economic activities, communal organization,family life, and material civilization of the medieval world’s ArabicspeakingJews. Indeed, with patience and a creative imagination, IndiaTraders of the Middle Ages could lay the foundation for taking this subdisciplinein new directions ...